Engineering high-Q superconducting tantalum microwave coplanar waveguide resonators for compact coherent quantum circuit - Shima Poorgholam-Khanjari; Valentino Seferai; Paniz Foshat; Calum Rose; Hua Feng; Robert H. Hadfield; Martin Weides; Kaveh Delfanazari (Scientific Reports)
Abstract Tantalum (Ta) has recently received considerable attention in manufacturing robust superconducting quantum circuits. Ta offers low microwave loss, high kinetic inductance compared to aluminium (Al) and niobium (Nb), and good compatibility with complementary metal-oxide-semiconductor (CMOS) technology, which is essential for quantum computing applications. Here we demonstrate the fabrication engineering of thickness-dependent high-quality-factor (high- $$\:Q_{i}$$ ) Ta superconducting microwave coplanar waveguide resonators. All films are deposited on high-resistivity silicon substrates at room temperature without additional substrate heating. Before Ta deposition, a niobium (Nb) seed layer is used to promote a body-centred cubic lattice ( $$\:α\:$$ -Ta) formation. We further engineer the kinetic inductance ( $$\:L_{K}$$ ) of the resonators by varying Ta film thicknesses. High $$\:L_{K}$$ is a key advantage for applications because it facilitates the realisation of high-impedance, compact quantum circuits with enhanced coupling to qubits. The maximum internal quality factor $$\:Q_{i}$$ of $$\:\sim\:$$ 3.6 × 106 in the high power regime and $$\:Q_{i}$$ of $$\:\sim\:$$ 4.5 × 105 in the single-photon regime is achieved for 100 nm Ta which represents an improvement over previous room-temperature deposited Ta resonators on silicon substrates in the single photon regime, while the highest kinetic inductance of 0.6 pH/sq is obtained for the thinnest film, which is 40 nm. This combination of high $$\:Q_{i}$$ and high $$\:L_{K}$$ highlights the potential of Ta microwave circuits for high-fidelity operation of compact quantum circuits.